ISOTOPIC COMPOSITION OF CARBON IN OILS OF THE CHUKOTKA PENINSULA - Kudryavtseva Y.I.; Krylova T.A.; Dertev A.K.; Blokhina G.G.; Makhov S.F. (My University, 1990)
The isotopic composition of carbon in oils and condensates of the Chukotka Peninsula was studied in samples taken from wells on the verkhne-Tekelay, Verkhne-Echinskaya, and Izmennaya tracts, located in the southern part of the Anadyr Basin Only one sample was studied from well 31 of the Uglovaya tract, in the Khatyr Basin. All of the oils were derived with Paleogene-Neogone elastic reservoirs. This is the first time that the isotopic composition of the carbon in these oils has been investigated; the objective was to cast light on oil migration.
Keywords: Paleogene; Cenozoic::Paleogene; Кайнозой::Палеоген